Making a difference in educational inequality: reflections from research and practice. Issue 3 (3rd July 2022) - Cahill, Kevin; O'Sullivan, Dan
ABSTRACT: This article is a reflective, research-informed, commentary on educational disadvantage from two lecturers in Education who have spent large proportions of their professional lives working in 'DEIS' school settings before transitioning into teacher education. This reflection intends to problematise the concept of educational disadvantage and will then proceed to explore, through literature and some empirical findings, possibilities for changing paradigms of policy and practice in marginalised school settings. Most research and writing on educational disadvantage in Ireland has focused upon policy, statistics, and the problems that accompany marginalisation. We intend to explore possibilities for change at the level of policy and practice, considering interventions in terms of curriculum, pedagogy and assessment; and how we can address inequalities in educational experiences. We will explore possibilities around key areas such as: disrupting 'cultural deficit' theories and fixed ideas of ability related to educational disadvantage; consider nuanced intersectional understandings of inequalities in education; framing 'funds of knowledge' perspectives in curriculum, pedagogy and assessment; and encouraging critical pedagogical approaches amongst teachers. We are hopeful that this article will support teachers in schools, researchers and policy makers as they endeavour to make a difference in their work with marginalised communities.